Change of agitation power when emptying the tank for propeller impellers - Stelmach, Jacek; Kuncewicz, Czesław; Jirout, Tomas; Rieger, Frantisek (Chemical and Process Engineering, 2025)
In this study, the phenomenon of mixing power increase when emptying tanks with an operating propeller impeller was examined. The tests were carried out for impellers with wide and narrow blades in two geometrically similar tanks with diameters T = 545 mm and T = 300 mm equipped with four standard baffles. The varied mixing power during tank emptying was examined on a larger scale, and on a scale of T = 300 mm the distribution of axial and radial velocities in the vertical r - z plane was determined using the PIV system. A very large increase in mixing power was found when the liquid-free surface being lowered was close to the upper surface of the blades. In the limit case, as much as a three-fold increase in mixing power was observed compared to the mixing power in a tank completely filled. It was found that the increase in mixing power was caused by a change in the mode of liquid circulation in the mixing tank when the liquid surface approached the impeller area. Correlation equations determining the values of the mixing power increase factor φ depending on the geometric parameters of the impeller and the Froude number are given. The φ values for propeller impellers were compared with similar values obtained for other types of impellers.